DEVELOPMENT OF INTERACTIVE LEARNING MEDIA BASED ON SMART APPS CREATOR TO IMPROVE MATH LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Khairumnisa Putri Azizah; Erna Zumrotun; Wulan Sutriyani (JURNAL PEMBELAJARAN DAN MATEMATIKA SIGMA (JPMS), 2025)
This research aims to design interactive learning media using Smart Apps Creator, which is expected to improve students' mathematics learning outcomes regarding flat shapes. This study applies a Research and Development research approach using the ADDIE model as its methodology. This study involves 26 students in grade V from SDN 3 Mantingan as its subjects. The data collection techniques applied in this study include: 1) Results of material and media validation; 2) Questionnaires for teacher and student responses; 3) Learning outcome test questions in the form of multiple-choice pretest-posttest. Data analysis was conducted through the application of the N-gain tests and the paired sample t-test. The results of the study indicate that the product is rated as "Very Feasible" with a precentage of 87% from material experts and 93% from media experts. The teacher responsespracticality score reached 90% and the students 88% were in the, cate "Very Good" category. The N-gain test result of 0.76 which is categorized as high, while the paired sample t-test indicated a significant difference between the pre-test and post-test scores. This proves that interactive learning media is feasible, practical, and effective in improving mathematics learning outcomes.